Some aspects of biology of Alepes djedaba (Forsskal) from Vera val, Gujarat - Raje, S G (Indian Journal of Fisheries, 2011)
Random samples of A. djedaba were collected from the commercial landings of trawl and gill nets operated by mechanized boats at Veraval. Total length (mm), weight (g), sex ratio, maturity stage of females and gut contents were recorded from fresh samples. The maturity stages were classified according to I.C.E.S. system. For estimating the fecundity, 5% formalin-preserved ovaries in stage V were used. The food of the species was analysed by volumetric and occurrence methods. The index of preponderance was calculated by the method of Natarajan and Jhingran (1961).